To Be or Not to Be: The Entrepreneur in Endogenous Growth Theory - Magnus Henrekson; Dan Johansson; Johan Karlsson (Research Institute of Industrial Economics (IFN), 2021)
We examine the conceptualization of entrepreneurs in neo-Schumpeterian growth theory, which has reintroduced entrepreneurs into mainstream economics. Specifically, we analyze how neo-Schumpeterians relate to the contradiction between the entrepreneur-centered view of Schumpeter (1934) and the entrepreneurless framework of Schumpeter (1942), with the two frameworks entailing vastly different economic and policy implications. The analysis is based on a review of approximately 750 peer-reviewed articles over the period 1990-2018. The articles were identified using text mining methodology and supervised machine learning. The results show that the literature leans towards Schumpeter (1942); innovation returns are modeled as following an ex ante known probability distribution. By assuming that the outcomes of innovation activities are (probabilistically) deterministic, the Schumpeterian entrepreneur becomes redundant. In addition, the literature abstracts from genuine uncertainty, thus evading central issues regarding the economic function of the entrepreneur, especially with respect to disruptive innovations, ownership, and profits. To incorporate genuine uncertainty, the literature needs to adopt a broader conceptual foundation that goes beyond equilibrium modeling.
Keywords: O10; O30; B40; 330; Creative destruction; Economic growth; Entrepreneur; Innovation; Judgment; Bibliometric analysis; Knightian uncertainty